Evaluasi Kinerja Tata Kelola Teknologi Informasi pada PT. XYZ Menggunakan COBIT 2019 - Louis Ferdynan Wirawan; Johan Tambotoh (STMIK Banjarbaru, 2022)
PT. XYZ still has several problems such as data in the database that is not updated and not all employees are proficient in operating the existing Information Technology system. To ensure IT governance functions properly, our research aims to evaluate the performance of Information Technology governance at PT. XYZ is engaged in the corn cultivation industry and crop yield management, using COBIT (Control Objectives for Information and Related Technologies) 2019 as a model framework. The area used is Delivery, Service and Support, an area that evaluates the provision of information technology services and support, such as not updating database systems, human error, and server down. Respondents in this study depended on the resulting RACI graph. With the implementation of Information Governance Performance Evaluation, PT. XYZ can overcome its deficiencies and understand how to encourage the company's business development through the performance of Information Technology Governance to achieve its business goals. The findings in the form of survey results become recommendations and future recommendations to maximize the performance of IT governance at PT. XYZ.Keywords: Performance Evaluation; Information Technology Governance; COBIT 2019; Delivery; Service and Support AbstrakOperasional bisnis PT. XYZ masih memiliki beberapa kendala seperti data dalam database yang tidak update dan tidak semua karyawan mahir dalam mengoperasikan sistem Teknologi Informasi yang ada. Untuk memastikan tata kelola TI berfungsi dengan baik, penelitian kami bertujuan untuk mengevaluasi kinerja tata kelola Teknologi Informasi pada perusahaan PT. XYZ yang bergerak di bidang industri budidaya tanaman jagung dan pengelolaan hasil panen, dengan menggunakan COBIT (Control Objectives for Information and Related Technologies) 2019 sebagai kerangka model. Area yang digunakan adalah Delivery, Service and Support, area yang mengevaluasi penyediaan layanan dan dukungan teknologi informasi, seperti tidak memperbarui sistem basis data, kesalahan manusia, dan server down. Responden pada penelitian ini bergantung pada grafik RACI yang dihasilkan. Dengan penerapan Evaluasi Kinerja Tata Kelola Informasi, PT. XYZ bisa mengatasi kekurangan yang dimiliki dan memahami bagaimana mendorong pengembangan bisnis perusahaan melalui kinerja Tata Kelola Teknologi Informasi mencapai tujuan bisnisnya. Temuan berupa hasil survei menjadi rekomendasi dan rekomendasi kedepannya untuk memaksimalkan kinerja tata kelola TI pada PT. XYZ.